Cyberbullying and Cyber Dating Abuse in Students of a Private Mexican University - Romo-Tobón, Ricardo J. (2020)
The cyber-violence in adolescents and young people recently has attracted the attention of the scientific community, it is a relatively new and growing phenomenon that has developed along with the use of Information and Communication Technologies. Besides, data currently available in this subject in the Mexican context is still scarce. Therefore, this research analyzes the presence and association of cyberbullying and cyber-violence in the couplein a sample of 299 students from a private Mexican university (183 women and 116 men) who answered the Cyberbullying Questionnaire and the Cyber dating abuse questionnaire among young couples. According to the results obtained, the presence of both phenomena was observed, men reported suffering and perpetrating with greater frequency cyberviolence of couple in the direct aggression modality, in addition correlations were found between both phenomena. In conclusion, both women and men seemed to be victims and aggressors, especially in behaviors related to the control of the couple, also cyberbullying and cyber-violence were related, although with a lower strength of association.